PENGARUH PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP MINAT BELAJAR IPAS PADA SISWA KELAS IV SD NEGERI 1 ASTANA - Nunung Sunari; Hema Widiawati; Novan Hardiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using animated video media on interest in learning science in fourth grade students of SD Negeri 1 Astana. This type of research is quantitative research with experimental research method Preexperimental One Group Pretest-Posttest design. The population in this study were all fourth grade students totaling 87 students, while the sample was fourth grade students totaling 29 students. The sampling technique used in this study was Simple Random Sampling. The independent variable in this study was animated video media while the dependent variable was interest in learning. The research data were obtained by distributing learning interest questionnaires. The analysis technique was the Paired Sample T-test and the N-Gain test. Based on the results obtained using the paired sample T-test, a significance value of 0.000 <0.05 was obtained because based on decision making, Ha was accepted and Ho was rejected. While the results of the N-Gain test score average value of 0.7309, the effectiveness category of the N-Gain value was high, or it could be interpreted that the use of animated video media (effective) from the results obtained. Therefore, it can be concluded that there is a significant influence on the interest in learning science in fourth-grade students of SD Negeri 1 Astana. Thus, it can be concluded that there is an influence of the use of animated video media on the interest in learning science in fourth-grade students of SD Negeri 1 Astana.